Physical and performance characteristics of backs and forwards of the Rio Grande do Sul rugby team - Wilhelm Neto, Eurico Nestor (2019)
The aim of this study was to compare physical characteristics and performance parameters of Brazilian regional Rugby athletes, divided by player position. Total body mass, height, body mass index (BMI), yo-yo intermittent test level 1 (yo-yo test), vertical jump height, and bench press one repetition maximum (1RM) values were assessed in 15 forwards and 16 backs who formed the Rio Grande do Sul adult Rugby squad in 2010. Data were compared with the Student's T Test for independent measures, assuming α<0.05. Data show that forwards were heavier, stronger and displayed greater BMI compared to backs (p<0.05). The latter, however, performed better in the yo-yo intermittent recovery test 1 (p<0.05). The present results support position-specific \characteristics of backs and forwards according to their respective physiological demands, demonstrating that such differences are already apparent in competitive amateur athletes. The presented results may also provide reference values for coaches and regional athletes.